Optimising Learning Outcomes: A Comprehensive Approach to Virtual Simulation Experiment Teaching in Higher Education - Chang, Jing; Liu, Dong (International journal of human-computer interaction, 2025)
The development of online virtual simulation test teaching programs has recently been in increasing demand due to the lack of traditional test teaching resources in colleges. This research aims to optimize the delivery of experimental teaching in higher education by harnessing the potential of virtual simulation technology. However, several challenges and limitations must be addressed to attain optimal learning outcomes. Data collection methods encompassed questionnaire surveys, multi-subject interviews, and regression analysis to examine underlying issues and trends in this teaching approach. This study underscores three vital dimensions for enhancing virtual simulation experiment teaching in colleges. Firstly, the integration of online and offline teaching modes is essential to broaden the spectrum of test-teaching scenarios. Secondly, technological advancements are pivotal in bolstering the reliability and authenticity of virtual examinations. The incorporation of virtual reality and artificial intelligence significantly enhances the realism and accuracy of virtual experiments, making them more effective in simulating real-life scenarios. Lastly, adapting the teaching model to accommodate diverse levels and facets is crucial for optimizing student learning experiences and outcomes. Tailoring teaching strategies and methods to individual student needs fosters a more personalized learning experience. Additionally, the paper highlights the significance of evaluating the effectiveness of virtual simulation experiment teaching through various assessment methods, including formative and summative assessments. This evaluation process enables teachers to identify areas for improvement and refine teaching practices to achieve better learning outcomes for students. As a result, this research provides valuable insights into the potential of virtual simulation technology in higher education and offers a roadmap for its successful implementation. Virtual simulation integration boosts operational skills, tackles equipment constraints, and fosters learning via error observation and correction. Synchronous knowledge application drives practical use, sharpens critical thinking, and eases equipment operation. Integrating diverse virus programs into virtual networks deepens understanding of security principles and defense strategies. Online and offline integration widens the teaching scope, providing a versatile model beyond science and engineering disciplines. Virtual simulation broadens experiential learning, promoting adaptive teaching methodologies and skill development.